Endoplasmic reticulum as a target in cardiovascular diseases: Is there a role for flavonoids? - Keylani, Kimia; Arbab Mojeni, Fariba; Khalaji, Amirmohammad; Rasouli, Asma; Aminzade, Dlnya; Karimi, Mohammad Amin; Sanaye, Pantea Majma; Khajevand, Nazanin; Nemayandeh, Nasrin; Poudineh, Mohadeseh; Azizabadi Farahani, Mehdi; Esfandiari, Mohammad Ali; et al. (Frontiers in Pharmacology, 2023)
Flavonoids are found in natural health products and plant-based foods. The flavonoid's molecules contain a 15-carbon skeleton with the particular structural construction of subclasses. The most flavonoid's critical subclasses with improved health properties are the catechins or flavonols (e.g., epigallocatechin 3-gallate from green tea), the flavones (e.g., apigenin from celery), the flavanones (e.g., naringenin from citrus), the flavanols (e.g., quercetin glycosides from berries, onion, and apples), the isoflavones (e.g., genistein from soya beans) and the anthocyanins (e.g., cyanidin-3-O-glucoside from berries). Scientific data conclusively demonstrates that frequent intake of efficient amounts of dietary flavonoids decreases the chronic inflammation and chance of oxidative stress expressing the pathogenesis of human sicknesses like cardiovascular disease. The endoplasmic reticulum (ER) is a critical organelle that plays a role in protein folding, post-transcriptional conversion, and transportation, which plays a critical part in keeping cell homeostasis. Various kinds of stimuli can lead to creating unfolded or misfolded proteins in the endoplasmic reticulum and then arise in ER stress. Constant ER stress triggers unfolded protein response (UPR), which ultimately causes apoptosis and diseases. Research has shown that ER stress plays a critical part in the pathogenesis of several cardiovascular diseases (CVD), such as diabetic cardiomyopathy ischemic heart disease, heart failure, aortic aneurysm, and high blood pressure. ER stress could be one of the crucial points for the cure of multiple CVD. In this review, we decided to summarize recent findings on flavonoids’ effects on the endoplasmic reticulum and their role in the prevention and treatment of cardiovascular diseases.